Adapting to change: Prioritising management for the future of the Marine Scalefish Fishery. (September 2018) - Nursey-Bray, Melissa; Magnusson, Anders; Bicknell, Nathan; Magnusson, Meagan; Morison, Julian; Sullivan, Andrew
Abstract: Marine scalefish fisheries face multiple challenges including management and sustainability pressures. These are going to be amplified by climate change. This paper reports on a project that used the Analytical Hierarchy Process (AHP) and semi-structured interviews to assess how marine scalefish fishers in South Australia, prioritise management objectives with a view to incorporating those views into structural industry reform to build the fishery's capacity to adapt in the face of these challenges. The project found that fishers, despite differences in geographical scale, fishing practice and species harvested, prioritised governance objectives most highly, and that economic and environmental objectives were prioritised as key and equally important; one could not exist without the other. Fishers prioritised social objectives the least as they expect these to follow from the economic and environmental objectives. Fishers also felt stocks had declined and that reform was urgently needed. Most fishers agreed that reform should include a reduction in licences. All fishers felt that recreational fishing was under-regulated and compromised commercial fishing opportunities. The project revealed that the capacity of fishers to adapt within the current operating environment is limited and that they will need government and other support to implement reform. For policy makers, this highlights that reform is culturally palatable but that it must include incentives and compensation for fishers to leave or stay in the industry. Highlights: Analytical Hierarchy Process and semi-structured interviews used for consultation. Fishers prioritised governance objectives most highly. Economic and environmental objectives were ranked as equally important. Social objectives, contrary to expectation ranked as lowest priority. Culturally palatable management is needed to build adaptive capacity of fishers.